A modified struvite and preparation method thereof

By modifying the use of lignin sulfonate on the surface of struvite, the existing flame retardant pollution problems and low efficiency of ball milling methods are solved, and efficient and environmentally friendly flame retardant performance and good thermal stability are achieved.

CN116835554BActive Publication Date: 2025-02-28NANJING TECH UNIV

Patent Information

Application Number
CN202310713771.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2025-02-28
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

Existing flame retardants are prone to contamination of water and soil after use, and the ball milling method produces ultrafine struvites with low efficiency and high energy consumption, and may lead to decomposition and dissolution of struvites.

Method used

By modifying the lignin sulfonate on the surface of the struvite, a modified struvite with a particle size distribution of 85% between 1 and 10 μm was formed, and the preparation was performed by mixing an alcohol solution with a magnesium salt and adjusting the pH of phosphate and ammonium salt.

Benefits of technology

Modified struvite has high flame retardant properties, low solubility and good thermal stability. It can form a dense fire-resistant coating. The nitrogen, phosphorus and magnesium ions released after use can be absorbed by plants and will not pollute the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a modified struvite and a preparation method thereof, wherein the surface of the struvite is modified by lignin sulfonate, and at least 85% of the particle size distribution is between 1 and 10 μm. The slurry formed by the modified struvite and water has excellent film-forming properties, can more easily adhere to the surfaces of various substrates and oily leaves to form a dense and uniform fireproof coating, maximizes the contact area with the attached object, and improves the flame retardant effect of the struvite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of flame retardant materials, and particularly relates to a modified struvite flame retardant material and a preparation method thereof. Background Art

[0002] Affected by global warming, the frequency of forest fires is increasing rapidly around the world. Forest fires cause serious damage to the ecological environment and natural resources, threaten the lives of wild animals, and even endanger human life and property. Therefore, the research on forest fire prevention and flame retardant is of great significance to forest safety.

[0003] Water has always been the main fire extinguishing substance. In addition, chemical flame retardants are also an effective fire extinguishing substance that can reduce the intensity and spread of fire. Some countries have begun to widely use flame retardants to fight forest fires. Flame retardants can be divided into short-term and long-term types. Foam flame retardants are a type of short-term flame retardant. They are cheap and can make water extinguish fires with higher efficiency, but the effectiveness of foam flame retardants is much lower than that of long-term flame retardants. For long-term flame retardants, water only plays a minor role as a carrier. The active substance is mainly flame retardants. Even if the water evaporates, the flame retardant is still active. At present, the commonly used long-term flame retardants for forest fire prevention mainly include low-polymerization ammonium polyphosphate (APP), diammonium phosphate, monoammonium phosphate and ammonium sulfate. Although these flame retardants have good flame retardant properties, they are extremely water-soluble and easily pollute rivers and groundwater, causing eutrophication of water bodies, and also acidifying and hardening the soil, threatening the growth and reproduction of plants and soil microorganisms. Therefore, there is still a need to develop efficient flame retardants with ecological compatibility.

[0004] Struvite (MgNH4PO4·6H2O) is not only an efficient nitrogen and phosphorus slow-release fertilizer, but also a new type of efficient, environmentally friendly green inorganic flame retardant, so it is more suitable for outdoor or forest fire fighting. Seyed et al. deposited the synthetic struvite on cotton fabric by multiple baths, and the struvite showed ideal flame retardant and fireproof properties [POLYM-PLASTTECHNOL, 2008, 47(3): 307-312]. Guo et al. mineralized struvite in natural porous wood structures by vacuum impregnation and other methods, and the wood mineralized by struvite had excellent fire resistance [ACS Applied Materials & Interfaces, 2019, 11(5): 5427-5434.]. Although struvite has excellent flame retardant properties, the particle size of struvite has an important influence on the flame retardant properties. Liang et al. ball-milled struvite into ultrafine powder with an average particle size of 5 μm, and confirmed that the fire extinguishing speed of ultrafine struvite is faster than that of ammonium polyphosphate [Materials, 2022, 15: 8021.]. Although ball milling can make struvite reach the state of ultrafine powder, ball milling is not conducive to the industrial production of ultrafine struvite powder. First, ball milling has low efficiency and high energy consumption; second, the heat generated by ball milling will cause struvite to decompose (struvite will decompose above 80°C); third, the solubility of ultrafine struvite in water increases greatly, and the N and P elements produced will still pollute rivers and groundwater. Therefore, it is still necessary to develop ultrafine, non-soluble struvite with good flame retardant properties and related preparation methods. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a modified struvite and a preparation method thereof.

[0006] The invention provides a modified struvite, the surface of which is modified by lignin sulfonate, and at least 85% of the particle size distribution is between 1 and 10 mu m.

[0007] In the technical invention scheme of the present invention, the lignin sulfonate may be one or more of sodium lignin sulfonate, magnesium lignin sulfonate or alkali lignin; preferably, sodium lignin sulfonate.

[0008] The invention also provides application of the modified struvite in preparing a flame retardant.

[0009] The present invention also provides a method for preparing the modified struvite, comprising:

[0010] (1) mixing an alcohol solution and a magnesium salt to obtain a mixed solution A;

[0011] (2) mixing phosphate and ammonium salt, adding lignin sulfonate aqueous solution, mixing evenly, and adjusting the pH to 8.5-9.0 with an inorganic base to obtain a mixed solution B;

[0012] (3) Slowly add the mixed solution A to the mixed solution B, stir and maintain the pH value of the solution unchanged, mature, filter, wash, and dry at low temperature to obtain the target product.

[0013] In the technical invention scheme of the present invention: the alcohol solution is an aqueous solution of alcohol, and the alcohol can be one or more of methanol, ethanol or propanol.

[0014] In some embodiments, the alcohol solution described in the present invention is an alcohol solution of 5 to 160 g / L, preferably an alcohol solution of 8 to 142 g / L. The inventors have found that the addition of alcohol at an appropriate concentration can obtain an ultrafine struvite product with a more uniform particle size. If the concentration of the alcohol solution is too high or too low, it will affect the particle size distribution of the struvite product.

[0015] In the technical invention scheme of the present invention: the magnesium salt can be one or more of magnesium chloride, magnesium bicarbonate or magnesium acetate.

[0016] In the technical invention scheme of the present invention, Mg in the mixed solution A formed in step (1) 2+ The molar concentration is 0.01 to 0.15 mol / L, preferably 0.016 to 0.12 mol / L.

[0017] In the technical invention scheme of the present invention, the lignin sulfonate may be one or more of sodium lignin sulfonate, magnesium lignin sulfonate or alkali lignin; preferably, sodium lignin sulfonate.

[0018] In some embodiments, the concentration of the lignin sulfonate aqueous solution is 1-20 g / L.

[0019] In the technical invention scheme of the present invention: the phosphate can be one or more of sodium dihydrogen phosphate dihydrate, disodium hydrogen phosphate dodecahydrate, sodium phosphate, potassium hydrogen phosphate, potassium dihydrogen phosphate trihydrate or potassium phosphate.

[0020] In the technical invention scheme of the present invention: the ammonium salt can be one or more of ammonium bisulfate, ammonium chloride, and ammonium bicarbonate.

[0021] In the technical invention scheme of this invention: PO4 in the mixed solution B formed in step (2) 3- The molar concentration is 0.02~0.2mol / L.

[0022] In the technical invention scheme of the present invention: step (3) the mixed solution A is slowly added to the mixed solution B, Mg 2+ PO4 3 With NH4 +The molar ratio is (0.5-1.5): (1-2): 1, preferably (0.8-1.2): (1-2): 1. In the technical invention scheme of the present invention: the inorganic base used to adjust the pH can be a conventional inorganic base in the art, such as sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate solution, and the molar concentration is usually 0.2-0.5 mol / L, preferably sodium hydroxide.

[0023] In the technical invention scheme of the present invention, the aging, filtering, washing and low-temperature drying in step (3) can be carried out according to the conventional methods in the art, the aging time is usually 10 to 20 minutes, the drying temperature is usually 40 to 80°C, the drying time is 8 to 12 hours, and the preferred drying temperature is 45 to 60°C and the drying time is 10 hours. The inventors have found that a drying temperature exceeding 80°C will cause ammonia to escape from the struvite crystals or change the crystal form, thereby reducing the flame retardant activity of the struvite (such as Figure 8 (shown by the thermogravimetric loss of struvite at room temperature ~800°C).

[0024] The struvite provided by the present invention has high flame retardancy, is green and pollution-free, and has a simple preparation process. Compared with the prior art, it has the following beneficial effects:

[0025] (1) The present invention can achieve in-situ modification by adding lignin sulfonate in a simple one-step method. The obtained lignin sulfonate-modified struvite can obtain a modified struvite with a particle size distribution of 85% between 1 and 10 μm, which can not only greatly slow down the dissolution of ultrafine struvite, but also greatly improve the flame retardancy and thermal stability of the product.

[0026] (2) The slurry formed by the modified struvite and water has excellent film-forming properties and can more easily adhere to the surfaces of various substrates and oily leaves to form a dense and uniform fire-retardant coating, maximizing the contact area with the attached objects and improving the flame retardant effect of the struvite.

[0027] (3) The lignin sulfonate-modified struvite of the present invention can not only be used as a fire retardant, but also the nitrogen, phosphorus and magnesium ions slowly released after use can be promptly absorbed by the roots of plants and serve as fertilizer for the plants without causing pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The XRD diagrams of the products obtained in Example 1 and Comparative Example 1 of the present invention;

[0029] Figure 2 The Raman graphs of the products obtained in Example 1 and Comparative Example 1 of the present invention;

[0030] Figure 3 This is a particle size analysis diagram of the product obtained in Example 1 of the present invention;

[0031] Figure 4 It is the dissolution diagram of the product obtained in Example 1 of the present invention and Comparative Example 1;

[0032] Figure 5 is a SEM image of the product obtained in Example 1 of the present invention on a wood chip;

[0033] Figure 6 This is a SEM image of the product obtained in Comparative Example 1 of the present invention on a wood chip;

[0034] Figure 7 This is a flame retardant effect diagram of the wood chips obtained in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention;

[0035] Figure 8 This is a thermogravimetric loss (TG) diagram of the product obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0036] In order to further illustrate the present invention, the preparation of the modified struvite of the present invention is further described in detail below in conjunction with the examples. The following examples are convenient for better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified. The test materials used in the following examples are purchased from conventional biochemical reagent stores unless otherwise specified.

[0037] Example 1

[0038] According to the molar ratio of magnesium chloride hexahydrate, sodium dihydrogen phosphate dihydrate and ammonium chloride of 1:1.5:1, 118g / L of ethanol and magnesium chloride were mixed to obtain a mixed solution A, wherein the molar concentration of magnesium chloride hexahydrate was 0.02mol / L; sodium dihydrogen phosphate dihydrate, ammonium chloride and 85ml of deionized water were mixed, and then 2.5g / L of sodium lignin sulfonate was added and mixed evenly, and then the pH was adjusted to 9.0 with a NaOH solution to obtain a mixed solution B, wherein the molar concentration of sodium dihydrogen phosphate was 0.03mol / L, and the mixed solution A was slowly poured into the mixed solution B, and the solution pH was maintained at 9.0. When the pH was stable, it was aged for 15min, and the obtained precipitate was filtered and washed. Finally, the precipitate was dried at 45°C for 10 hours to obtain the target product.

[0039] Comparative Example 1

[0040] Weigh magnesium chloride hexahydrate, sodium dihydrogen phosphate dihydrate and ammonium chloride in a molar ratio of 1:1.5:1, mix 15 ml of deionized water with magnesium chloride to obtain a mixed solution A, wherein the molar concentration of magnesium chloride is 0.02 mol / L; mix sodium dihydrogen phosphate dihydrate, ammonium chloride and 85 ml of deionized water evenly, and adjust the pH to 8.5 with NaOH solution to obtain a mixed solution B, wherein the molar concentration of sodium dihydrogen phosphate is 0.03 mol / L, slowly pour the mixed solution A into the mixed solution B, maintain the solution pH at 8.5, when the pH is stable, mature for 15 minutes, filter and wash the obtained precipitate. Finally, dry the precipitate at 45°C for 10 hours to obtain the target product.

[0041] The differences between other embodiments and Example 1 are shown in Table 2, and the differences between other comparative examples and Comparative Example 1 are also shown in Table 1 (except Comparative Examples 1 and 2, the others are modified struvite):

[0042] Table 1 Examples and Comparative Examples

[0043]

[0044]

[0045] Effect experiment:

[0046] 1. Product Features

[0047] The products were subjected to XRD and Raman analysis, respectively. Figure 1 and Figure 2 As shown, the XRD results show that the products of Example 1 and Comparative Example 1 are both struvite (MgNH4PO4·6H2O). The Raman analysis results show that only the product of Comparative Example 1 has the Raman characteristic peak of MgNH4PO4·6H2O, while there is no Raman peak in Example 1. Therefore, it can be proved that lignin sulfonate exists on the surface of the product of Example 1, which covers the Raman characteristic peak of struvite. Laser particle size analysis of the product of Example 1 is performed, as shown in FIG. Figure 3 As shown, 85% of the particle size distribution is between 1-10 μm, and the median particle size is about 3.8 μm. The dissolution effect of Example 1 (modified struvite) and Comparative Example 1 (rod-shaped struvite) was tested by salicylic acid spectrophotometry. Figure 4 As shown, the NH4 + The dissolution rate was 1.13 mmol / L lower than that of comparative example 1 (rod-shaped struvite), which was 43% lower. The distribution of Example 1 (modified struvite) and comparative example 1 (rod-shaped struvite) on the wood chips was observed by scanning electron microscopy, as shown in FIG. Figure 5 and Figure 6As shown, compared with Comparative Example 1 (rod-shaped struvite), which has gaps in its film formation, Example 1 (modified struvite) has better film-forming properties, is more evenly distributed and denser on the wood chips, and has better flatness.

[0048] 2. Flame retardancy test

[0049] Prepare 4 pieces of wood of the same size (35×100×1.5mm 3 , S = 35cm 2 , 3.0±0.05g), the first wood chip was used as a blank sample, and the other three were used as experimental samples. The first blank wood chip was coated with deionized water on both sides, the second wood chip was coated with 0.2g of rod-shaped struvite (MAP) of comparative example 1 on both sides, and the third wood chip was coated with 0.2g of unmodified struvite (D 50 =1-10 μm), 0.2 g of modified struvite in Example 1 was coated on both sides of the fourth wood chip, and dried under a fume hood for 12 h. The dried wood chip was clamped on an iron frame, the wood chip was kept horizontal and 14 cm away from the desktop, the alcohol lamp wick was 1 cm away from the wood chip, and the blank sample and three wood chips coated with different struvite were burned in a closed and windless environment, each group was burned for 70 s, and ventilation was performed after the experiment.

[0050] The combustion of three wood chips, namely, blank wood chips, rod-shaped struvite coated with comparative example 1, unmodified struvite coated with comparative example 2, and modified struvite coated with example 1, was compared. Figure 7 As shown, the area calculation is shown in Table 2. Compared with the wood chips of Comparative Examples 1 and 2, the surface of the wood chips coated with the modified struvite of Example 1 is smoother and flatter, and the film-forming and paving properties are better. Within the same burning time, the wood chips coated with the modified struvite of Example 1 have the largest remaining burning area, and the flame retardant effect is as high as 73%, which is 35% and 21% higher than that of Comparative Examples 1 and 2, respectively. During the burning process, the wood chips coated with the modified struvite of Example 1 did not deform, and the modified struvite did not fall off or crack seriously. It can be seen that the modified struvite of the present invention has a good flame retardant effect.

[0051] Table 2 Calculation of flame retardant area (total area of ​​wood chips = 35 cm 2 )

[0052]

[0053]

Claims

1. A modified struvite, characterized in that: The surface of the struvite is modified by lignin sulfonate, and at least 85% of the particle size distribution is between 1 and 10 μm; the modified struvite is obtained by the following steps: (1) mixing an alcohol solution and a magnesium salt to obtain a mixed solution A; (2) mixing the phosphate and the ammonium salt, adding the lignin sulfonate aqueous solution, mixing evenly, and adjusting the pH to 8.5 to 9.0 with an inorganic base to obtain a mixed solution B; (3) Slowly adding the mixed solution A to the mixed solution B, stirring and maintaining the solution pH unchanged, aging, filtering, washing, and low-temperature drying to obtain modified struvite.

2. The modified struvite according to claim 1, characterized in that: The lignin sulfonate is one or more of sodium lignin sulfonate or magnesium lignin sulfonate.

3. The modified struvite according to claim 2, characterized in that: The lignin sulfonate is sodium lignin sulfonate.

4. Use of the modified struvite according to any one of claims 1 to 3 in the preparation of flame retardants.

5. The method for preparing the modified struvite according to claim 1, characterized in that: The steps include: (1) mixing an alcohol solution and a magnesium salt to obtain a mixed solution A; (2) mixing phosphate and ammonium salt, adding lignin sulfonate aqueous solution, mixing evenly, and adjusting the pH to 8.5-9.0 with an inorganic base to obtain a mixed solution B; (3) Slowly add the mixed solution A to the mixed solution B, stir and maintain the pH value of the solution unchanged, mature, filter, wash, and dry at low temperature to obtain the target product.

6. The preparation method according to claim 5, characterized in that: The alcohol solution is an aqueous solution of alcohol.

7. The preparation method according to claim 6, characterized in that: The alcohol is one or more of methanol, ethanol or propanol.

8. The preparation method according to claim 5, characterized in that: The alcohol solution is 5-160 g / L alcohol solution.

9. The preparation method according to claim 8, characterized in that: The alcohol solution is 8-142 g / L.

10. The preparation method according to claim 5, characterized in that: The magnesium salt is one or more of magnesium chloride, magnesium bicarbonate or magnesium acetate.

11. The preparation method according to claim 5, characterized in that: Mg in the mixed solution A formed in step (1) 2+ The molar concentration is 0.01~0.15mol / L.

12. The preparation method according to claim 5, characterized in that: Mg in the mixed solution A formed in step (1) 2+ The molar concentration is 0.016~0.12mol / L.

13. The preparation method according to claim 5, characterized in that: The lignin sulfonate is one or more of sodium lignin sulfonate or magnesium lignin sulfonate.

14. The preparation method according to claim 13, characterized in that: The lignin sulfonate is sodium lignin sulfonate.

15. The preparation method according to claim 5, characterized in that: The concentration of the lignin sulfonate aqueous solution is 1-20 g / L.

16. The preparation method according to claim 5, characterized in that: The phosphate is one or more of sodium dihydrogen phosphate dihydrate, disodium hydrogen phosphate dodecahydrate, sodium phosphate, potassium hydrogen phosphate, potassium dihydrogen phosphate trihydrate or potassium phosphate; the ammonium salt is one or more of ammonium hydrogen sulfate, ammonium chloride and ammonium bicarbonate.

17. The preparation method according to claim 5, characterized in that: PO4 in the mixed solution B formed in step (2) 3- The molar concentration is 0.02~0.2mol / L.

18. The preparation method according to claim 5, characterized in that: Step (3) Mixture A is slowly added to mixture B, Mg 2+ PO4 3- With NH4 + The molar ratio is (0.5~1.5):(1~2):

1.

19. The preparation method according to claim 18, characterized in that: Mg 2+ PO4 3- With NH4 + The molar ratio is (0.8~1.2):(1~2):

1.

20. The preparation method according to claim 5, characterized in that: In step (3), the aging time is 10 to 20 minutes, the drying temperature is 40 to 80° C., and the drying time is 8 to 12 hours.

21. The preparation method according to claim 20, characterized in that: The drying temperature is 45-60°C.

22. The preparation method according to claim 20, characterized in that: The drying time is 10h.

Citation Information

Patent Citations

  • Slow and fast release fertilizer composition and methods for making same

    CN105452197A

  • Novel mixed fertilizer of microbial agent and struvite and preparation method thereof

    CN114656300A

Cited By

  • Fire extinguishing powder based on seed crystal induced struvite and preparation method thereof

    CN121317841A